Effectiveness of an educational program on Nurses' Practices toward Nursing Management of Patients with Transurethral Resection of the Bladder Tumor in Hilla Teaching Hospitals - Halima Yusuf Al-Rubaiyee; Basim Hasson Hussein (Kufa Journal for Nursing Sciences)
Background: the standard first-line treatment for non-muscle invasive bladder cancer is transurethral resection of bladder tumor (TURBT), followed by instillation of intravesical chemotherapy. The goal of TURBT is to make a correct diagnosis and to remove all visible lesions. Several organizations have published reports on the importance of nursing staff understanding disease process and treatments leading to an improvement in quality of care. Improving the practice process is important to nursing as it improves nursing process, which improves patient outcomes.